Aetiopathogenicity Of Ulcerative Disease In Koi Carp, Cyprinus Carpio Linnaeus - Butprom, Sureerat (2004)

(untitled)
A chronic persistent ulcerative lesion of the skin in Koi carp (Cyprinus carprio L.) was reported in several commercial aquarium shops in Klang Valley. A study was conducted to chart the epizootiology and pathogenicity of the disease and its aetiological agents which included histopathological, bacteriological, virological and experimental infection. Thirty-six diseased Koi carps with skin ulcer were examined. Findings showed that the ulcerative lesion development involved the deep muscle layers showing tissue necrosis and inflammation in chronic lesions. The fish abdomen was filled with a clear or red-tinged ascitic fluid. The liver and kidneys were pale in colour, swollen and friable. In the histopathological study, lesions were found in the skin, gill, kidneys, liver, spleen and intestine. The changes were characterized by diffuse haemorrhages, cell degeneration and necrosis in the skin, liver and kidneys. Lamellar epithelial cells showed hyperplasia and hypertrophy at the base of gill lamellae. Depositions of haemosiderin were seen in kidneys, liver, hepatopancreas and spleen. In the intestine, haemorrhage in the tunica propria and atrophy of mucosal epithelium were seen. Electron microscopy revealed two type of virus like particles which were associated with the histopathological changes in the kidneys. The virus-like particles were presumably coronavirus and reovirus based on their morphology. Morphological and biochemical characteristics of bacteria isolated from the diseased Koi were determined by routine biochemical tests in combination with the BBL Crystal KitTM. In the present study, Gram-negative non-lactose fermenting rods were isolated from the skin lesions and kidneys. In total, 11 bacteria species were identified and Aeromonas hydrophila was the dominant species isolated from the fish in this study. The other species of the ulcer-associated bacteria were (i) Shewanella putrefaciens, (ii) Vibrio cholerae, (iii) Pseudomonas diminuta, (iv) Chryseobacterium meningosepticum, (v) Empedobacter brevis, (vi) Pseudomonas aeruginosa, (vii) Pantoea agglomerans, (viii) Enterobacter sakazakii, (viiii) Morganella morganii and (x) Aeromonas veronii. Primary cell cultures were initiated from the brain, gonad and kidneys of goldfish (Carassius auratus) by using trypsinization technique. The cells were cultured in Leibovitz-15 (L-15) medium supplemented with 10 to 20% fetal calf serum (FCS) and L-glutamine. The primary cell cultures from brain and gonad tissues were successfully established and reached monolayer confluence within 15 to 30 days. The attachment efficiency was serum-dependent though increasing FCS concentration did not stimulate further growth of cells. Virological examinations of ulcerated tissues on the primary cell cultures and established cell line, FHM, were negative for cytopathic effect (CPE) even after three blind passages of 10 days interval. Aeromonas hydrophila, S. putrefaciens and V. cholerae isolated from natural Koi carp with skin ulcer were used in experimental infection. The fish were injected 0.1 ml bacteria suspension at 1x107 cfu/ml. Bacteria were reisolated from ulcerative lesion and kidneys and had the same biochemical characteristics as those isolated from naturally infected fish. Ulcers began to appear three post infection as small and flat lesions. No apparent mortality was observed in all groups during the 30 days of the experiment. Histopathological studies revealed that A. hydrophila individually or in combination with other bacteria could have caused the small superficial ulcerative lesions. Haemorrhages and inflammation were seen in spleen, adipose tissue and kidneys. While individually or in combination, injection of S. putrefaciens and V. cholerae displayed localized lesion which was restricted only to the injection site. In conclusion, ulcerative lesion in Koi carp was primarily caused by multiple infection of several bacteria species, although the possibility of viral involvement must not be ruled out.